Beneath a scarlet sky : a novel - Sullivan, Mark T (Lake Union Publishing, 2017)
In 1940s Italy, teenager Pino Lella joins an underground railroad helping Jews escape over the Alps and falls for a beautiful widow, he also becomes the personal driver of one of the Third Reich's most powerful commanders.